Shape Effect of Polymer-Based Multilayer Microcapsules on Cellular Internalization - Zhang, Xiaoqiang (Langmuir : the ACS journal of surfaces and colloids, 2024)
The intracellular fate of drug carriers had received extensive attention, which was profoundly influenced by the shapes of carriers. However, it has not been fully addressed due to the lack of effective strategies to prepare carriers with different shapes and the interference of other parameters (such as stiffness and chemistry of the shaped particle and the different cell lines). In this work, polymer-based microcapsules with different shapes (spherical, peanut, dumbbell, and cubic) but the same surface chemistry were engineered through the alternative deposition of polyethylenimine (PEI) and polyethylene glycol (PEG) onto the sacrificial CaCO3 templates with different well-defined shapes. Various techniques (SEM, CLSM, AFM, FTIR, and XPS) were utilized to determine the shapes and chemical composition of these microcapsules. The effect of microcapsule shape on cellular internalization kinetics and the endocytosis mechanism was thoroughly studied, and dumbbell and cubic microcapsules showed greater internalization rates and amounts than spherical and peanut microcapsules. These microcapsules were internalized through micropinocytosis, and the shapes had no obvious effect on the endocytosis mechanism. This work provides a wealth of information about the relationship between the shape of microcapsules and their performance in cellular internalization, which will be of great help in the development of related drug carriers